Profetyzm Jezusa w tradycji synoptycznej (Przegląd Religioznawczy – The Religious Studies Review, 2023)
A community of disciples materialised around Jesus. What was the motive for following him? Who did they think he was? This fundamental question has been perpetuated by tradition, and was posed by Jesus himself to the disciples at Caesarea Philippi (Mk 8:27−30; Mt 16:13−20; Lk 9:18−21). Among the answers, all the synoptics present the view of the people that Jesus was a prophet. One of the reasons people came to Jesus was that he was considered as such. Although Mark the evangelist knows that people regard Jesus as a prophet (Mk 8:28), he reserves this role for John the Baptist (Mk 1:4−7). Jesus, on the other hand, is depicted as the son of man, destined for the cross, only to reveal himself to the world at that moment (8:31−33; 9:30−32; 10:32−34). Matthew the evangelist aims to show Jesus as a follower of Moses, who rejects the Pharisaic interpretation of the Law and fulfils the law through the proclamation of the Gospel based on the principle of love. In this context, Jesus appears as a prophet who announces a new Torah-Gospel. Jesus’ message is collated in five great speeches in which the main principles of the Kingdom of God will be proclaimed in the Sermon on the Mount (Matthew 5:1−7:28). Luke the evangelist shifts the emphasis by presenting Jesus in a saviour role, to liberate people from sin and open the space of heaven. Jesus is portrayed as the deliverer from sin from his inauguration appearance in Nazareth on the Sabbath (probably on Yom Kipppur) (Luke 4:16−30) to the proclamation of salvation on the ‘Good Thief ’ on the cross (Luke 23:43). This convention of salvation includes the idea of Jesus the Prophet making a sacrifice for our sins on the cross ‘because it is impossible for a prophet to perish outside of Jerusalem’ (Luke 13:33).